Analisis Perbandingan Bunga Dalam Kredit Di PT. BPR Berkah Serumpun Mandiri Provinsi Kepulauan Bangka Belitung - Nila Selviana; Meilis Tiara; Winiarsih Winiarsih; Meidia Natasya; Rolenci Rolenci; Reni Humairah (CV. ITTC INDONESIA, 2025)
This study aims to analyze and compare the loan interest burden using three calculation methods: flat interest, compound interest, and effective interest rate at PT. BPR Berkah Serumpun Mandiri in Pangkalpinang, Bangka Belitung Province. A quantitative approach with a descriptive-comparative method was applied, using secondary data sourced from the official 2025 Multi-Purpose Loan brochure. Six loan samples were examined based on variations in loan amount and term. The findings indicate that the flat interest method results in fixed monthly installments of approximately 16%, yet fails to reflect the actual interest burden. The compound interest method shows a gradual decline in annual rates as the loan term increases. In contrast, the effective interest rate provides the most accurate representation of real borrowing costs, reaching up to 32% for shorter terms. These results emphasize the importance of transparent interest information and financial literacy to enable borrowers to make informed credit decisions.